Advancement in surgery - a review - Kumar, Amres (The Indian Journal of Animal Sciences, 2012)
Significant progress has been made during last 5 decades in the areas of anaesthesia and analgesia, general surgery, gastrointestinal surgery, orthopaedic surgery, urogenital surgery and radiology in India. Surgical techniques for effective and better management of patients suffering from various surgical disorders of these systems have been developed and perfected and analgesic/anaesthetic techniques have been developed for various regions of the body and in the management of patients suffering from various disease disorders. Diagnostic techniques developed for various surgical diseases have made it possible for early diagnosis of the diseases to reduce morbidity and mortality. The diagnostic and surgical techniques developed have greatly helped in the better management of surgical patients and to increase animal productivity in the country.